Hematological, morphological and morphometric characteristics of blood cells from rhea, Rhea Americana (Struthioniformes: Rheidae): a standard for Brazilian birds - S. S. M. Gallo; N. B. Ederli; M. O. Bôa-Morte; F. C. R. Oliveira (Brazilian Journal of Biology)
Abstract Blood exams are an indispensable tool in bird medicine. This study aimed at describing values and aspects of rheas' hematology, Rhea americana, as well as analyzing the morphology and morphometry of all blood cells. Fifty eight adult rheas of both sexes from two farms, one in Cachoeiro de Itapemirim, Espírito Santo State and the other in São Carlos, São Paulo State, were selected. Blood samples were taken and RBC count, PCV and Hb levels measured and used in hematimetric indexes calculations. The total and differentiated leukocyte counts, as well as the TPP and fibrinogen were determined. Erythrocytes, leukocytes and thrombocytes were identified and characterized morphologically. The values for the red series and hematimetric indexes were: RBC (2.81±0.15×106/μL), PCV (44.20±2.86%), Hb (12.12±0.74 g/dL), MCV (15.75±0.89 fL), MCH (43.18±1.82 pg), MCHC (27.44±0.80 g/dL); the values of white series were: WBC (12.072±4116/μL), heterophils (64.10±9.90%), eosinophils (2.05±2.06%), monocytes (6.40±2.99%), lymphocytes (26.93±9.62%), basophils (0.52±1.27%). One may conclude that on average, rheas' blood cells are larger than those of other birds, but these cells in smears cannot be differentiated only by their size. Besides rheas' leukocytes have different components and coloring as in other bird species, however, there are no components or staining aspects unique to the species.